Optimasi Parameter Desain Multi-Cell Hexagonal Crash Box terhadap Absorbsi Energy Impact dengan Metode Taguchi - Rismanto, Muhammad; Choiron, Moch. Agus; Sugiono, Sugiono (Jurnal Rekayasa Mesin, 2020)
The crash box is a passive safety system placed between the bumper and the mainframe of the car that functions as an energy absorber to reduce the impact of driving accidents. The purpose of this study is to determine the optimal level of factors and analyze the factors that provide the most significant effect on energy absorption in a multi-cell hexagonal crash box. Identification of parameters that affect the crash box in energy absorption, namely: the position of placement hole (P), the distance of position hole (L), the thickness of crash box (t), and the hole diameter (D). The modeling method has used the design of the crash box by utilizing a computer simulation with software ANSYS 17.0. This research uses aluminum material type AA 6061-T4 and impactor material uses structural steel. Modeling loading using the frontal crash test method. In this modeling, the impactor with a speed of 7.67 m/s with a deformation length of 100 mm. This research uses the experimental design of the Taguchi method with the L27 orthogonal array. The optimization result were obtained optimum design parameter multi-cell hexagonal crash box with parameter settings P = inner wall; L = 112.5 mm; t = 2 mm, and D = 6.6 mm. Based on the calculated F value â‰¥ F Table, the factors P, t, and D affect the ability to absorb energy. Thickness crash box (t) has the highest contribution of 98.10% in increasing the value of energy absorption.